Teacher’s Perceptions of Self-regulated Learning and Motivation - Mousa, Anass (Revue Internationale du Chercheur, 2023)
Through the Teacher Perception of Student Self-Regulated Learning (TPSRL) survey, the present paper aims to investigate teachers' assessments of their students' self-regulated learning (SRL) skills, examining factors influencing these evaluations, the perceived correlation between SRL competence and academic performance, and teachers' preferences for instructing different types of learners. Designed to address the inherent limitations of self-reported surveys, the TPSRL survey employs a multi-method, multi-source empirical approach. A total of 30 randomly sampled university language professors belonging to different public and private universities participated in this study. Findings reveal three key themes: teachers' overall recognition of SRL's importance for autonomous learning; limited emphasis on their role in teaching SRL techniques; and challenges such as students' expectations for prescriptive materials, the difficulty of instructing heterogeneous self-regulated learners, lack of training, and curriculum constraints. These insights underline the need for professional development to enhance teachers' understanding and implementation of SRL strategies across diverse classroom contexts, ensuring a more effective promotion of self-regulated learning.